2015
DOI: 10.3390/ma8074162
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Mechanical Properties with Specific Wear Rate and the Coefficient of Friction of Graphite/Epoxy Composites

Abstract: The correlation between the mechanical properties of Fillers/Epoxy composites and their tribological behavior was investigated. Tensile, hardness, wear, and friction tests were conducted for Neat Epoxy (NE), Graphite/Epoxy composites (GE), and Data Palm Fiber/Epoxy with or without Graphite composites (GFE and FE). The correlation was made between the tensile strength, the modulus of elasticity, elongation at the break, and the hardness, as an individual or a combined factor, with the specific wear rate (SWR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Moreover, under the applying load, the mechanical properties differ at contact points . These mechanical properties also play a significant role in the friction behavior of composite polymers; the higher tensile strength and elongation at break result in a lower coefficient of friction …”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, under the applying load, the mechanical properties differ at contact points . These mechanical properties also play a significant role in the friction behavior of composite polymers; the higher tensile strength and elongation at break result in a lower coefficient of friction …”
Section: Introductionsupporting
confidence: 91%
“…26 These mechanical properties also play a significant role in the friction behavior of composite polymers; the higher tensile strength and elongation at break result in a lower coefficient of friction. 32 In general, there are factors, which affect wear and friction of elastomers and polymers. Review of literature shows that statistical studies regarding the effect of external process parameters on wear are mostly focused on polymers and their composites, 4,33-35 while wear and friction behavior of rubbers are more complex because their wear mechanism differs significantly under variable conditions.…”
mentioning
confidence: 99%
“…The standard epoxy matrix has a two-component with bisphenol A, based resin, AW 106 and an amine-based hardener, HV 953IN. The standard epoxy resin was chosen as matrix material owing to its greater mechanical strength, higher thermal stability, and negligible dimensional shrinkage on curing, high viscosity and density than the other thermoset polymer resins like polyester [15]. Graphene, with properties such as flexibility, transparency, ultra-strength, elastic nature, scalable, transferable, corrosion resistance, electrically conducting etc., has evolved and dominated the materials world.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the interaction of furan resin and wear debris of graphite was useful to reduce the wear rate of furan resin-Gr composite. Alajmi et al [42] investigated the correlation between mechanical properties with specific wear rate and the coefficient of friction of Gr-epoxy composites. They concluded that 2 of 13 graphite led to eclectic effects on mechanical properties of graphite/epoxy composites at the same time as affirmative effects on tribological properties of graphite/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%